Media Sosial, Online Costumer Review dan Digital Payment terhadap Minat Beli Pengguna Marketplace Tiktok di Surakarta - Puspita, Alvina Della; Sarsono; Istiqomah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and explain the influence of social media, online customer reviews and digital payments on the buying interest of Tiktok marketplace users in Surakarta. The research method uses a quantitative approach, in the form of a questionnaire. The population in this study were all Surakarta City residents who had made purchases on the Tiktok application and a total sample of 100 respondents was taken using a purposive sampling technique. The data used in this study are primary data in the form of questionnaires filled out by respondents. The analytical method used is quantitative analysis, multiple linear regression, F test, t test and the coefficient of determination with the SPSS version 21 program. The results of this study indicate that social media, online customer reviews and digital payments have a positive and significant effect on purchase intention. Purchase intention can be explained by social media variables, online customer reviews and digital payments of 63.6%, while the rest is explained by other variables, for example, content marketing, brund trust, social media influencers, product reviews and others. Keywords : purchase interest, social media, online customer review, digital payment.